Bilingues Prozeßprotokoll, ChLA XLI 1188 + SPP XX 283 (= ChLA XLV 1325) - Hagedorn, Dieter; Hagedorn, Ursula (Wiener Papyri, 2001)
Zusammensetzung und Neuedition der Fragmente ChLA XLI 1188 + SPP XX 283 (= ChLA XLV 1325)